Seleksi Cekaman Kekeringan Secara In Vitro Tunas Jagung Putih (Zea mays L.) Menggunakan PEG - Yustiningsih, Maria; Poto, Amanda; Ledheng, Ludgardis (BIO-EDU: Jurnal Pendidikan Biologi, 2021)
This study aims to identify the morphology response of white corn (Zea mays L) shoots explant on in vitro drought stress selection using Polyethylene glycol (PEG). The study was conducted at the Biology Education Laboratory, University of Timor using a Completely Randomized Design (CRD) with three treatment concentrations of PEG, namely PEG 0 gr/L (control), PEG 5 gr/L, and 15 gr/L. The explants grown on Murashige & Skoog (MS) basal media with PEG according to the treatment concentration. Parameters observed were root length, shoot height and plant biomass to see plant response to drought stress. Data were analyzed using SPSS and further test using DMRT. The results showed that the concentration of PEG gradually could affect plant growth, especially shoot height. PEG concentration of 5 gr/ml and 15 gr/ml was the highest shoot growth (2,625 cm) when compared to PEG 0 gr/L (1.47) which indicated that explants could still grow under drought stress conditions. However, both treatments showed no effect of PEG on root length and biomass which could indicate growth inhibition in the given selection. Based on the results it can be concluded that PEG selection can affect the growth rate of white corn shoots and growth inhibition.